PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PRODUK SCARLETT WHITENING - Doni Dirgantara Asikin (JURNAL BISNIS dan TEKNOLOGI, 2023)
This research was conducted on consumers of scarlett whitening products at the marketplace shopee scarlett whitening official shop in West Bandung Regency. The purpose of this study is to see the effect of brand image and product quality on customer satisfaction on Scarlett Whitening products. The sample in this study were 100 people. The researcher used judgment sampling method and used questionnaires to collect data. The results of the validity and reliability test using the Pearson Product Moment and Alpha Cronbach correlation methods, it is known that the items made are valid and reliable. The calculation is carried out using SPSS Version 25. The results of the calculation can be seen that the value of the influence of the brand image variable on customer satisfaction partially is 38.5%. Then the magnitude of the effect of the product quality variable on customer satisfaction partially is 39.9%. The results of calculating the value of the influence of brand image variables and product quality variables on customer satisfaction of scarlett whitening products in the marketplace sopee scarlett whitening official shop in West Bandung Regency simultaneously by looking for the coefficient of determination shows how much influence between the two variables studied can be seen from the R value of 0.884 . This value shows a positive value between the brand image and product quality variables on customer satisfaction, meaning that the better the brand image and product quality will create good customer satisfaction. The magnitude of the R square number is 0.782, this means that it shows the influence of brand image and product quality on customer satisfaction by 78% while the remaining 22% is influenced by other factors.